2007
DOI: 10.1002/pmic.200600919
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of both extracellular and intracellular proteins is involved in the lethal or nonlethal phenotypic variation of BrtlIV, a murine model for osteogenesis imperfecta

Abstract: This study used proteomic and transcriptomic techniques to understand the molecular basis of the phenotypic variability in the bone disorder osteogenesis imperfecta (OI). Calvarial bone mRNA expression was evaluated by microarray, real-time, and comparative RT-PCR and the bone proteome profile was analyzed by 2-DE, MS, and immunoblotting in the OI murine model BrtlIV, which has either a moderate or a lethal OI outcome. Differential expression analysis showed significant changes for eight proteins. The expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
53
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 45 publications
6
53
1
Order By: Relevance
“…42 We recently described ER stress in Brtl fibroblast and calvarial bone, as well as in MSCs differentiating toward the osteoblastic lineage. [30][31][32] In the latter case, we showed an increase in HSP47, a specific molecular chaperone known to bind folded type I procollagen molecules in the ER, similar to previous reports in some OI cases. 43 Thus, we evaluated the expression of HSP47 following silencing and found a significant reduction in F-Mut shRNA-transduced Brtl cells, compared with control fibroblasts, as might be expected based on about 40% total collagen suppression.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…42 We recently described ER stress in Brtl fibroblast and calvarial bone, as well as in MSCs differentiating toward the osteoblastic lineage. [30][31][32] In the latter case, we showed an increase in HSP47, a specific molecular chaperone known to bind folded type I procollagen molecules in the ER, similar to previous reports in some OI cases. 43 Thus, we evaluated the expression of HSP47 following silencing and found a significant reduction in F-Mut shRNA-transduced Brtl cells, compared with control fibroblasts, as might be expected based on about 40% total collagen suppression.…”
Section: Discussionsupporting
confidence: 90%
“…The expression level of the target gene was normalized to the housekeeping gene Gapdh (Mm99999915_g1, Applied Biosystems) and the relative expression was calculated using the DDCt method. The evaluation of the specific expression of each Col1a1 allele was then performed by means of allele-specific real-time PCR as described in Forlino et al 30 Collagen analysis F-Mut shRNA transduced and parental Brtl fibroblasts were plated (2.5 Â 10 5 /3 cm Petri dishes) and allowed to adhere for 24 h. Collagen synthesis was stimulated by incubating the cells for 24 h before protein recovery with 100 mg/ml sodium ascorbate in DMEM containing 1% FBS. Type I collagen was extracted and purified from media and cell layer as described previously.…”
Section: Rna Isolation and Real-time Allele-specific Pcrmentioning
confidence: 99%
“…In untreated animals from our colony, BrtlIV pups had a survival rate 2 times lower compared with WT and, at the same age of 2 months, 65.5% were WT and 34.5% were heterozygous BrtlIV, consistent with previous reports. 20,41 The significantly higher (P ϭ .04) proportion of surviving BrtlIV animals in transplanted mice indicated that the treatment rescued the genotype-related lethality in our murine model.…”
Section: Iut Of Total Bone Marrow Cells Into Brtl and Wt Embryosmentioning
confidence: 99%
“…45,46 From the intensities of the ␣1(I)-S-S-␣1(I) and ␣1(I) bands, we estimated the fraction of collagen molecules with 2 mutant chains as 26.7% plus or minus 4.3% in trabecular and 25.7% plus or minus 2.5% in cortical bone from untreated animals, consistent with previous reports. 41,46 In treated animals, this fraction decreased with increasing bone marrow engraftment of donor cells ( Figure 4B). In animals with the highest engraftment (1.9% Ϯ 0.1%), this fraction was 20.4% plus or minus 2.9% in trabecular and 20.9% plus or minus 2.6% in cortical bone (P Ͻ .05; Figure 4 and supplemental Table 2).…”
Section: Collagen Composition In Treated and Untreated Bones From Brtmentioning
confidence: 99%
See 1 more Smart Citation